Mechanics, function, pain and effects of exercise intervention among nurses with low back pain in Hospital Universiti Sains Malaysia - Rahman, Nur Athirah Abd (2024)
Low back pain (LBP) is classified as a leading disabling musculoskeletal disorder that affects all range of the population globally and nursing is a high-risk group profession associated with LBP. However, previous studies on LBP among nurses did not quantify the mechanics during nurses-related tasks across subtypes which hinders the understanding of how these tasks cause LBP. Besides that, previous studies on exercise therapy in individuals with chronic non-specific LBP (CNLBP) were focused on pain score, muscle power and function but none on the long-term effects of exercise on full body mechanics among female nurses with CNLBP. The significance of this study compared with previous studies was the comparison of full body mechanics among female nurses with CNLBP. This research comprised of two studies that aim: 1) to compare the full body mechanics between healthy nurses and those with CNLBP and 2) to evaluate the effects of exercise intervention on CNLBP among female nurses. In study 1, 26 female nurses were recruited (Healthy Group, n=13 and CNLBP Group, n=13) and their full body mechanics, functional disability outcomes and pain score were compared. Based on the results, CNLBP participants employed greater lumbar flexion during walking (p<0.05), greater lumbar flexion during sit-to-stand (STS) (p<0.05), greater lumbar flexion (p=0.01) and decreased vertical ground reaction force (VGRF) (p=0.01) during carry and transfer (CNT) compared to healthy participants. This motion caused the upper body to move towards the load and decreased the VGRF, hence, indirectly applied narrow base transfer technique. Furthermore, increase in lumbar flexion during walking and STS among CNLBP participants was common as this pattern was manifested as the compensatory mechanism to avoid pain caused by increasing of trunk stiffness. For study 2, 54 female nurses were randomised into three groups (Control Group, n=18, Lumbar Stabilisation Exercise (LSE) Group, n=18 and Lumbar Muscles Strengthening Exercise (LMSE) Group, n=18). LSE and LMSE groups exercised for two sessions in a week for 8 weeks whereas, control group was given a diary to record their daily activities and 24 hours diet recall. Participants completed four assessments which were pre- (before), middle- (during 4th weeks), post- (after eight weeks) intervention and one month follow up measurements. Three dimensional (3D) full body kinematics and kinetics of walking, STS and CNT, trunk muscle power (extensor), sit-and-reach, functional disability, pain intensity and trunk flexor endurance were tested. One month follow up showed LMSE had slightly increased in lumbar flexion (p<0.05), centre of pressure (COP) (p=0.01) and ankle abduction (p=0.04) during walking, lumbar flexion (p<0.05), VGRF (p=0.02) and knee flexion (p=0.04) during CNT and lumbar flexion (p=0.01) during STS than post-intervention. We concluded that LMSE is more effective in long-term effects than LSE in reducing LBP among nurses.